SOLVING ECONOMIC PROBLEMS USING DIFFERENTIAL EQUATIONS (International journal of artificial intelligence, 2025)
This article highlights the role and importance of differential equations in modeling modern economic processes. It analyzes time-dependent economic indicators such as population growth, price dynamics, investment efficiency, and changes in production volume using mathematical models. The application of first-order differential equations is demonstrated using real examples such as the Solow economic growth model, the Malthus population model, and the price equilibrium model. In addition, the process of accumulating interest on a bank deposit savings strategy is modeled using a differential equation. The graphs presented in the article visually illustrate the changes in economic indicators over time. At the end of the study, the use of differential equations as an effective tool in economic analysis and forecasting is emphasized.